2017
DOI: 10.1002/2016ja023778
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution of neutral wind shear associated with sporadic E layers derived from GAIA

Abstract: There have been a number of papers reporting that the statistical occurrence rate of the sporadic E (Es) layer depends not only on the local time and season but also on the geographical location, implying that geographical and seasonal dependence in vertical neutral wind shear is one of the factors responsible for the geographical and seasonal dependence in Es layer occurrences rate. To study the role of neutral wind shear in the global distribution of the Es layer occurrence rate, we employ a self‐consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 56 publications
(120 reference statements)
6
61
0
Order By: Relevance
“…Li et al () showed the effect of ENSO on gravity wave activity and related changes to the background atmosphere in the MLT. Combining these results with those of Shinagawa et al (), we attempt to deduce whether an ENSO modulation on the background atmosphere between 90 and 110 km would be consistent with our COSMIC observations on the ENSO modulation of E s . Li et al () actually focus during Boreal winter.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Li et al () showed the effect of ENSO on gravity wave activity and related changes to the background atmosphere in the MLT. Combining these results with those of Shinagawa et al (), we attempt to deduce whether an ENSO modulation on the background atmosphere between 90 and 110 km would be consistent with our COSMIC observations on the ENSO modulation of E s . Li et al () actually focus during Boreal winter.…”
Section: Discussionsupporting
confidence: 57%
“…This study utilizes S 4 indices between 90 and 110 km. This region is known to exhibit significant variations in vertical wind shear due to both the general circulation and a wide spectrum of atmospheric waves particularly atmospheric tides (Shinagawa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al 15 (2014) employed the COSMIC measurements to study the global morphology of E s OR and the result of theoretical simulations suggested that the E s OR seasonal variation is likely attributed to the convergence of metallic ion flux caused by the vertical wind shear. Shinagawa et al (2017) calculated the global distribution of the vertical ion convergence and showed that the local and seasonal variations in the wind shear distribution could partially account for the geographical and seasonal variation of E s OR. 20 There have been a lot of papers reporting the geographical distribution and seasonal variation of global E s layers retrieved from GPS RO signals, and nearly all these works were on the occurrence rate of E s layers.…”
mentioning
confidence: 99%
“…They found that wind shear theory satisfactorily explains the summer Es maximum, although their metallic ion distribution also maximises in summer, which is broadly in correspondence with qualitative results by Haldoupis et al (2007) who compared meteor rates with Es occurrence rates (OR). Shinagawa et al (2017) analyzed the global distribution of vertical ion convergence based on GAIA Earth system model predictions. They showed that the ion convergence distribution is broadly consistent with Es OR.…”
Section: Introductionmentioning
confidence: 99%
“…Note however, that at higher midlatitudes the DT amplitudes become small compared with SDT ones during most of the year. Owing to its smaller amplitude, the quarterdiurnal tide (QDT) has been analyzed less frequently in the past (Smith et al, 2004), but more recently has attained increasing attention (Liu et al, 2015;Azeem et al, 2016;Jacobi et al, 2017Jacobi et al, , 2018aGuharay et al, 2018;Gong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%